Disequilibrium Econometrics on Micro Data - Bouissou, M. B.; Laffont, J. J.; Vuong, Q. H. (Review of Economic Studies, 1986)
This paper brings some empirical evidence to the construction of a more disaggregated view of disequilibrium. Individual data on firms collected by INSEE through periodic Business Surveys are used to construct the distribution of firms over the four possible disequilibrium regimes. Then the behavior of this distribution over time is analyzed by estimating dynamic conditional logit models on panel data.